Analysis of Financial Performance in the Activity Management Unit (UPK) of Sukamantri District, Ciamis Regency in the Year 2019-2021 - Fitriani; Ridwan Hakiki (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine how financial performance is based on the financial ratios Loans at Risk (LAR), Ponofolio at Risk (PAR), Return on Investment (ROI), and Cost Coverage (CCr) at the Sukamantri District Activity Management Unit (UPK) in 2019-2021. The research method used in this research is quantitative descriptive method. The data used in this study are primary data obtained from interviews and secondary data obtained from documents and archives at UPK Sukamantri District. The results of this study indicate that the financial performance of the Sukamantri District UPK in 2019-2021. Based on the results of the ratio (Loans at Risk) LAR is satisfactory in 2019, 2020 is satisfactory and in 2021 is minimal, the ratio (Ponofolio At Risk) PAR in 2019 - 2021 is satisfactory, the ratio (Return On Investmen) ROI in 2019 - 2021 is satisfactory and the ratio (Cost Coverage) CCr in 2019 - 2021 is satisfactory